Pertumbuhan dan Hasil Jagung Manis terhadap Sistem Budidaya Secara Organik dan Anorganik - Utami, Rizky Septika; Gustian, Meko; Togatorop, Eny Rolenti; Sari, Dia Novita (UNIB Press, 2025)
The study aimed to observe the growth and yield of sweet corn in organic and inorganic cultivation systems. The experimental design in the study used a completely randomized block design with three replications. The treatments consisted of organic and inorganic cultivation systems. Observations included variables on growth components and yield components. Observation data were analyzed statistically using the t-test (Paired Two Sample for Means at P < 0,05). The results showed that sweet corn fertilized organically and inorganically had the same effect on growth components (plant height, stem diameter, number of leaves, leaf length, leaf area, and leaf greenness) and yield components (cob height, cob length, and cob diameter with husks, cob length, cob diameter, and cob weight without husks, number of rows in the cob and number of seeds per row). Farmers can use the results of this study to choose fertilizers for cultivating sweet corn.